Towards the Visualisation of Collaborative Policy Decomposition - CONLAN, OWEN; KEENEY, JOHN; LEWIS, DAVID; O'SULLIVAN, DECLAN; WADE, VINCENT PATRICK (IEEE, 2008)
Policy-based management is typically used to manage large and complex systems, e.g. the management of telecommunications networks. When collaborating multi-disciplinary managers try to create policies from their own viewpoint they are hindered by a lack of a common vocabulary and an inability to understand how the complex system currently operates and how it is constrained. For example, modern telecoms networks must be constrained by many different types of policies, including: operational policies, legal policies, billing and provision polices etc.. As the policy-set grows, and more cross-domain managers write policies, the system becomes unwieldy, static and stale. This is due to a lack of overall understanding of how the system is currently operating in a constrained manner. We propose to empower collaborating managers by building user-centric semantically informed visualisations of the managed system's dynamic state and constraints. These visualisations and control adaptation mechanisms will be tailored to each manager's context and domain thereby facilitating ongoing cooperative management and communication between collaborating managers.
PUBLISHED
Keywords: collaborative policy; decomposition visualisation; cooperative management; user-centric semantically informed visualisations; policy-based management telecommunications network management